Impact of SO2 and light on chemical morphology and hygroscopicity of natural salt aerosols - Xiangrui Kong; Cheng Wu; Harsh Raj Mishra; Yuxin Hao; Mathieu Cazaunau; Antonin Bergé; Edouard Pangui; Robin Faust; Wanyu Liu; Jun Li; Sen Wang; Bénédicte Picquet-Varrault; et al. (Atmospheric Environment, 2024)

Implications of management on immunogenetic variation in the European grayling (Thymallus thymallus) - Jana Huml; Martin Taylor; W. Harris; Robin Sen; Jonathan Ellis (Frontiers in Marine Science, 2019)

Climate change: Risk and mitigation strategies for European grayling (Thymallus thymallus) - Jana Huml; W. Harris; Martin Taylor; Robin Sen; Jonathan Ellis (Frontiers in Marine Science, 2019)

Neutral variation does not predict immunogenetic variation in the European grayling ( Thymallus thymallus) —implications for management - J. Vanessa Huml; Martin I. Taylor; W. Edwin Harris; Robin Sen; Jonathan S. Ellis (Molecular Ecology, 2018)
Preservation of genetic diversity is critical to successful conservation, and there is increasing demand for the inclusion of ecologically meaningful genetic information in management decisions. Supportive breeding programmes are increasingly implemented to combat declines in many species, yet their effect on adaptive genetic variation is understudied. This is despite the fact that supportive breeding may interfere with natural evolutionary processes. Here, we assessed the performance of neutral and adaptive markers (major histocompatibility complex; MHC ) to inform management of European grayling ( Thymallus thymallus ), which routinely involves supplementation of natural populations with hatchery‐reared fish (stocking). This study is the first to characterize MH II DAA and DAB loci in grayling and to investigate immune genetic variation in relation to management practice in this species. High‐throughput Illumina sequencing of “introduced,” “stocked native” and “non‐stocked native” populations revealed significantly higher levels of allelic richness and heterozygosity for MH markers than microsatellites exclusively in non‐stocked native populations. Likewise, significantly lower differentiation at the MH II than for microsatellites was apparent when considering non‐stocked native populations, but not stocked populations. We developed a simulation model to test the effects of relaxation of selection during the early life stage within captivity. Dependent on the census population size and stocking intensity, there may be long‐term effects of stocking on MH II , but not neutral genetic diversity. This is consistent with our empirical results. This study highlights the necessity for considering adaptive genetic variation in conservation decisions and raises concerns about the efficiency of stocking as a management practice.

Arbuscular mycorrhizal community structure on co-existing tropical legume trees in French Guiana - Francis Q. Brearley; David R. Elliott; Amaia Iribar; Robin Sen (Plant and Soil, 2016)

Niche partitioning of bacterial communities in biological crusts and soils under grasses, shrubs and trees in the Kalahari - David R. Elliott; Andrew D. Thomas; Stephen R. Hoon; Robin Sen (Biodiversity and Conservation, 2014)

Medium-term fertilization of grassland plant communities masks plant species-linked effects on soil microbial community structure - Stavros D. Veresoglou; Andreas P. Mamolos; Barry Thornton; Olga K. Voulgari; Robin Sen; Demetrios S. Veresoglou (Plant and Soil, 2011)

Glomus intraradices and Gigaspora margarita arbuscular mycorrhizal associations differentially affect nitrogen and potassium nutrition of Plantago lanceolata in a low fertility dune soil - Stavros D. Veresoglou; Liz J. Shaw; Robin Sen (Plant and Soil, 2011)

Placement of attine ant-associated Pseudonocardia in a global Pseudonocardia phylogeny (Pseudonocardiaceae, Actinomycetales): a test of two symbiont-association models - Ulrich G. Mueller; Heather Ishak; Jung C. Lee; Ruchira Sen; Robin R. Gutell (Antonie van Leeuwenhoek, 2010)

Gopi Krishna Podila - Robin Sen (Mycorrhiza, 2010)

ITS rDNA sequence-based phylogenetic analysis of Tomentellopsis species from boreal and temperate forests, and the identification of pink-type ectomycorrhizas - Urmas Kõljalg; Hanna Tammi; Sari Timonen; Reinhard Agerer; Robin Sen (Mycological Progress, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)